Delamanid Resistance: Update and Clinical Management - Nguyen, Thi Van Anh; Anthony, Richard M; Cao, Thi Thu Huyen; Bañuls, Anne-Laure; Nguyen, Van Anh Thi; Vu, Dinh Hoa; Nguyen, Nhung Viet; Alffenaar, Jan-Willem C (Clinical infectious diseases, 2020)
Delamanid, a-first-in-class bicyclic nitroimidazole, was recently approved for multidrug-resistant tuberculosis treatment. Pitted against the hope for improving treatment outcomes is the threat of the rapid resistance emergence. This review provides information on the mechanisms of action, resistance emergence, and drug susceptibility testing (DST) for delamanid. Delamanid resistance has already been reported in both in vitro experiments and clinical settings. Although mutations conferring delamanid resistance have been identified in fbiA, fbiB, fbiC, ddn, and fgd1 genes of Mycobacterium tuberculosis, knowledge about the molecular resistance mechanisms is limited, and there remains no standardized DST method. The rapid acquisition of delamanid resistance emphasizes the need for optimal use of new drugs, the need for drug resistance surveillance, and a comprehensive understanding of drug resistance mechanisms. Further studies are necessary to investigate genetic and phenotypic changes that determine clinically relevant delamanid resistance to help develop a rapid delamanid DST.